Exploring the Effectiveness of Restorative Justice Practice in Criminal Law System - Yana Priyana; Abdul Aziz Assayuti; Muhamad Romdoni (West Science Law and Human Rights, 2023)
The criminal justice system in Indonesia, like many other countries, faces the challenge of effectively addressing crime while ensuring justice for victims and rehabilitation for offenders. In response to the limitations of the traditional punitive approach, restorative justice has emerged as an alternative paradigm, emphasizing healing, reconciliation, and community involvement. This research study aims to trace the effectiveness of restorative justice practices within the Indonesian criminal justice system through a comparative analysis. By employing a mixed-methods approach, the research combines quantitative data from official criminal justice statistics and qualitative data from interviews, case studies, and focus groups. The findings reveal that restorative justice cases demonstrate higher rates of victim engagement, increased offender accountability, and lower recidivism rates compared to conventional cases. Victims express higher levels of satisfaction with the restorative justice process, and practitioners acknowledge its potential benefits. However, challenges in implementation and the need for community support are also evident. The research contributes to the ongoing discourse on criminal justice reform in Indonesia and provides evidence-based insights to guide policymakers in developing a more balanced and effective approach to addressing crime and promoting justice, healing, and restoration within society.